Self-managed peer writing groups for the development of EFL students literacy practices - Rodas Brosam, Elisabeth L. (2021)
Peer response writing groups present several benefits in language learning classrooms. However, they are usually supervised by the instructor and thus become time consuming when carried out in class. This descriptive case study offers a model for extramural peer feedback and analyzes 12 meeting transcriptions of four undergraduate EFL writing groups implemented outside class time as support for an academic writing course with limited time for student interaction. These peer response groups were organized to: 1) provide participants with an additional audience, 2) open a space to practice the L2 in an authentic communicative situation, and 3) engage in peer review activities, a literacy practice associated with scientific-academic writing. Based on the data analysis of participant interactions, three main themes emerged according to what the members talked about: interacting as authors and reviewers of research articles, using the L2 in authentic communicative situations, and talking about and enacting literacy practices Although the experience of these writing groups was mainly positive, one of the limitations was their short lifespan, which prevented additional training to model peer response that would help facilitate the interaction among the participants, an important consideration to achieve beneficial peer feedback and to scaffold the process.